2020
DOI: 10.3390/polym12081724
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing and Solvent Dissolution Recycling of Polylactide–Lunar Regolith Composites by Material Extrusion Approach

Abstract: The in situ resource utilization of lunar regolith is of great significance for the development of planetary materials science and space manufacturing. The material extrusion deposition approach provides an advanced method for fabricating polylactide/lunar regolith simulant (PLA/CLRS-1) components. This work aims to fabricate 3D printed PLA–lunar regolith simulant (5 and 10 wt.%) components using the material extrusion 3D printing approach, and realize their solvent dissolution recycling process. The influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This requires significant up-mass of auxiliary equipment to allow for e.g., stripping and processing of topsoil, as well as the raw material for the binding resin. If, however, the binding agents (such as polyesters like polylactic acid) could also be derived or produced on-site from in situ resources, an additive manufacturing method may become immediately more feasible 79,80 .…”
Section: Production Of Materials For Manufacturingmentioning
confidence: 99%
“…This requires significant up-mass of auxiliary equipment to allow for e.g., stripping and processing of topsoil, as well as the raw material for the binding resin. If, however, the binding agents (such as polyesters like polylactic acid) could also be derived or produced on-site from in situ resources, an additive manufacturing method may become immediately more feasible 79,80 .…”
Section: Production Of Materials For Manufacturingmentioning
confidence: 99%
“…They also observed that, in the spectroscopic analysis, the recovered PLA’s molecular weight slightly decreased, but still, it was fully reusable. Such a promising result suggests that 3D printing could be a promising tool to solve the problem with limited space resources [ 34 ].…”
Section: Circular Application Of 3d Printing Wastementioning
confidence: 99%
“… Degradation modes of polylactide/lunar regolith stimulant (PLA/CLR-1) and spectral analysis of recovered and original PLA [ 34 ]. …”
Section: Figurementioning
confidence: 99%
“…In [ 34 ], effects of sterilizations on the mechanical behavior of 3D-printed ABS parts were studied. As this condition might be occurred for medical instruments in a hospital environment, instrument functionality can be changed.…”
Section: Introductionmentioning
confidence: 99%